Effect of Thermal Processing on Antinutrients in Common Edible Green Leafy Vegetables Grown in Ikot Abasi, Nigeria - Udousoro, Imaobong Inyang; Ekop, Roland U.; Udo, Efiok Johnson (Pakistan Journal of Nutrition, 2013)
The effects of time and temperature variation on the levels of anti-nutrients in five popularly consumed green leafy vegetables in Akwa Ibom State, Nigeria, were investigated. The vegetables were obtained from Ikot Abasi, Akwa Ibom State in Nigeria, and they included Utazi leaf (Gongronema latifolium), Bitter leaf (Vernonia amygdalina), Curry leaf (Ocimum canum sims) Bush apple leaf (Heinsia crinata) and Waterleaf (Talinum triangulare). The vegetables were subjected to heating conditions of 50°C and 90°C for 5 minutes and 15 minutes, and the levels of selected anti-nutrients (phytate, cyanides, tannins, oxalates) assessed. Heating conditions reduced the levels of all the investigated anti-nutrients in vegetables in the studies; the greatest reduction in level was observed in oxalates. In the vegetables, Talinum triangulare recorded the greatest reduction in anti-nutrients levels, tannins (84.4%), phytates (84.1%), cyanides (35.8%), total oxalate (57.1%) and soluble oxalate (75%). Heating at 90°C for 15 minutes was the most impacting for all the vegetables. The reduction of tannins ranged from 25.4 to 84.4%, phytates from 43.7 to 84.1%, cyanides from 22.1 to 40.7%, total oxalates from 57.1 to 75.0%, soluble oxalates from 66.7 to 78.3%. This study reveals that the most effective thermal processing temperature and time for anti-nutrient reduction in the selected vegetables was 90oC for 15 minutes. The data generated will help dieticians and other health workers in the formulation of different diets to meet the varied needs of patients in clinics and health establishments.